Low-Volume High-Intensity Interval Training in a Gym Setting Improves Cardio-Metabolic and Psychological Health - Shepherd, S.; Wilson, O.; Taylor, A.; Thøgersen-Ntoumani, Cecilie; Adlan, A.; Wagenmakers, A.; Shaw, C. (Public Library of Science, 2015)
Background - Within a controlled laboratory environment, high-intensity interval training (HIT) elicits similar cardiovascular and metabolic benefits as traditional moderate-intensity continuous training (MICT). It is currently unclear how HIT can be applied effectively in a real-world environment. Purpose - To investigate the hypothesis that 10 weeks of HIT, performed in an instructor-led, group-based gym setting, elicits improvements in aerobic capacity (VO2max), cardio-metabolic risk and psychological health which are comparable to MICT. Methods - Ninety physically inactive volunteers (42±11 y, 27.7±4.8 kg.m-2) were randomly assigned to HIT or MICT group exercise classes. HIT consisted of repeated sprints (15–60 seconds, >90% HRmax) interspersed with periods of recovery cycling (≤25 min.session-1, 3 sessions.week-1). MICT participants performed continuous cycling (~70% HRmax, 30–45 min.session-1, 5 sessions.week-1). VO2max, markers of cardio-metabolic risk, and psychological health were assessed pre and post-intervention. Results - Mean weekly training time was 55±10 (HIT) and 128±44 min (MICT) (p<0.05), with greater adherence to HIT (83±14% vs. 61±15% prescribed sessions attended, respectively; p<0.05). HIT improved VO2max, insulin sensitivity, reduced abdominal fat mass, and induced favourable changes in blood lipids (p<0.05). HIT also induced beneficial effects on health perceptions, positive and negative affect, and subjective vitality (p<0.05). No difference between HIT and MICT was seen for any of these variables. Conclusions - HIT performed in a real-world gym setting improves cardio-metabolic risk factors and psychological health in physically inactive adults. With a reduced time commitment and greater adherence than MICT, HIT offers a viable and effective exercise strategy to target the growing incidence of metabolic disease and psychological ill-being associated with physical inactivity.